HR Focus Within the Indian Information Technology Industry - Mahato, Madhuri (Prabandhan: Indian Journal of Management, 2012)
The world is witnessing a shift towards increased service orientation among organizations the world over. This increased service orientation has gained momentum since the advent of globalization and has more relevance in the Indian context because it has aided in the growth of India and the Indian IT industry, in particular. The growth in this sector has led to increased employment and has made it a key sector. In the light of the importance attached to this sector, coupled with its offering of lucrative employment opportunities in the present as well as in the future, an understanding of the HR focus within this industry has become a vital prerequisite.